Customer Loyalty: Quality of Service - Apri Budianto (Journal of Management Review, 2019)
This article focuses on the influence of service quality on customer loyalty to modern market customers. This article is motivated by the increasing number of modern market customers caused by the quality of service that affects the increasing loyalty of customers. The formulation of the problem in this article is how the quality of service influence on customer loyalty. The working hypothesis in this article is: "Service Quality positively affects customer loyalty".The method employed in making this article was done to get a picture of the effect of service quality on customer loyalty to modern market customers. Data were collected through data collection techniques in the field using explanatory survey method. Customer loyalty is influenced by the service quality of 38.30%. This means that customer loyalty is only affected a small portion of service Quality of 38.30%. Thus tcount> ttable was 3.421> 1.667. Then the null hypothesis (Ho) is rejected. This means that service quality has a positive effect on customer loyalty.Service Quality positively affects customer loyalty, meaning the better the quality of service provided the more loyal customers.